1996
DOI: 10.1038/hdy.1996.103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence and evolution of Polyommatus coridon gennargenti (Lepidoptera: Lycaenidae) in Sardinia

Abstract: Electrophoretic analysis of 17 enzyme loci was carried out to assess the genetic differentiation and isolation of the Sardinian Polyommatus coridon gennargenti from R c. apennina of peninsular Italy and the related taxon P caelestissimus from central Spain. I? c. gennargenti is represented by a small, strongly inbred population, restricted to the central mountains of Sardinia, and probably derived from mainland populations as indicated by the reduction of genetic variation (P 17.6 per cent, H 0.024) with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
(17 reference statements)
1
22
0
1
Order By: Relevance
“…Graur 1985;Packer et al 1998;Vandewoestijne et al 1999;. None of the parameters analysed reached the average diversities found in the highly diverse butterfly family of the Blues (Lycaenidae) (e.g., Leliè vre 1992;Peterson 1995;Marchi et al 1996;Brookes et al 1997;Schmitt and Seitz 2001;Schmitt et al 2003), but the observed values were considerably higher than in genetically impoverished taxa as species of the genus Yponomenta (Menken 1987) or Aglaope infausta (Schmitt and Seitz 2004). In comparison with Nymphalids, the studied Thymelicus species showed population genetic diversities that were little less than in common and widespread species of this family (e.g., Vandewoestijne et al 1999;Schmitt et al 2005), but considerably higher than in rare and very localised taxa (e.g., Debinski 1994;Britten et al 1994Britten et al , 1995Pelz 1995).…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 97%
“…Graur 1985;Packer et al 1998;Vandewoestijne et al 1999;. None of the parameters analysed reached the average diversities found in the highly diverse butterfly family of the Blues (Lycaenidae) (e.g., Leliè vre 1992;Peterson 1995;Marchi et al 1996;Brookes et al 1997;Schmitt and Seitz 2001;Schmitt et al 2003), but the observed values were considerably higher than in genetically impoverished taxa as species of the genus Yponomenta (Menken 1987) or Aglaope infausta (Schmitt and Seitz 2004). In comparison with Nymphalids, the studied Thymelicus species showed population genetic diversities that were little less than in common and widespread species of this family (e.g., Vandewoestijne et al 1999;Schmitt et al 2005), but considerably higher than in rare and very localised taxa (e.g., Debinski 1994;Britten et al 1994Britten et al , 1995Pelz 1995).…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 97%
“…The butterfly has very low genetic variation (mean heterozygosity, H=0.024, vs. H=0.185 of the mainland P. coridon) and significant genetic differentiation from mainland populations (Nei's coefficient of genetic distance D=0.434), suggesting that the Sardinian taxon is evolving independently from the mainland taxa (Marchi et al 1996). Larval stages feed exclusively on the perennial Hippocrepis comosa (L.) (Fabaceae), have extended development time, and hibernate.…”
Section: Study Systemmentioning
confidence: 99%
“…Indeed, the European P. coridon and other species of the former Lysandra group are thought to be sedentary (Shreeve 1992), and P. c. gennargenti adults have been observed flying only in the immediate vicinity of larval food plants (Casula et al 2004). Due to its strong specialization, low genetic variability, low mobility, and narrow and fragmented distribution, P. c. gennargenti has been considered vulnerable to extinction (Casula et al 2004;Grill et al 2002;Marchi et al 1996).…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…While the former is mostly accepted as being just a subspecies of P. coridon, the latter is frequently assumed to be a good species, as supported for example by genetic analysis and rearing experiments (Marchi et al 1996, Jutzeler et al 2003. Polyommatus corydonius is another morphologically similar species distributed in Turkey and the Caucasus region, but which never occurs in sympatry with P. coridon (Tshikolovets 2011).…”
Section: Closely Related Speciesmentioning
confidence: 99%